2009
DOI: 10.1371/journal.pone.0006277
|View full text |Cite
|
Sign up to set email alerts
|

The Special Neuraminidase Stalk-Motif Responsible for Increased Virulence and Pathogenesis of H5N1 Influenza A Virus

Abstract: The variation of highly pathogenic avian influenza H5N1 virus results in gradually increased virulence in poultry, and human cases continue to accumulate. The neuraminidase (NA) stalk region of influenza virus varies considerably and may associate with its virulence. The NA stalk region of all N1 subtype influenza A viruses can be divided into six different stalk-motifs, H5N1/2004-like (NA-wt), WSN-like, H5N1/97-like, PR/8-like, H7N1/99-like and H5N1/96-like. The NA-wt is a special NA stalk-motif which was fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
134
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(140 citation statements)
references
References 33 publications
4
134
0
2
Order By: Relevance
“…1a). The longer stalk region of the H5N1 NA has been shown to contribute to pathogenicity (Zhou et al, 2009). Here, we confirmed that removing this region reduced pathogenicity, with or without the PB1 M5 allele, by determining mean death time (MDT).…”
supporting
confidence: 73%
See 1 more Smart Citation
“…1a). The longer stalk region of the H5N1 NA has been shown to contribute to pathogenicity (Zhou et al, 2009). Here, we confirmed that removing this region reduced pathogenicity, with or without the PB1 M5 allele, by determining mean death time (MDT).…”
supporting
confidence: 73%
“…We have also described the improved growth and protein yield of a reassortant containing the H5N1 A/Vietnam/1203/2004 (A/VN/1203) HA segment and a chimeric NA segment comprising the C terminus (non-coding region and first 72 aa) from the A/ VN/1203 strain with the N terminus from PR/8 (Adamo et al, 2009). The stalk region of the NA protein differs between different influenza virus strains in both length and amino acid identity, and has been shown to affect growth, protein yield and pathogenesis (Adamo et al, 2009;Baigent & McCauley, 2001;Zhou et al, 2009). Here, we continued these studies by creating reassortants containing PB1 wt or PB1 m5 and the A/VN/1203 HA with either the WT (NA wt ) or chimeric (NA Ch ) NA from A/VN/1203.…”
mentioning
confidence: 99%
“…Castrucci and Kawaoka demonstrated in 1993 that mutated A/WSN/33 (H1N1) strains with a shortened stalk replicated poorly in eggs and did not cause systemic disease (18). In 2009 Matsuoka et al (19) and Zhou et al (20) both showed higher virulence of H5N1 viruses with longer NA stalks in chickens, but their studies reported varying effects in mice (19,20). Although isolates with the NA stalk deletion did grow, we did not proceed with them because of the importance of egg growth for current manufacturing of influenza vaccines.…”
Section: Discussionmentioning
confidence: 92%
“…The NA stalk of SC-H5N1 viruses had a 20 aa deletion (positions 49-68), which might enhance virus adaptation to domestic fowl and increase virulence in mammals (Cauldwell et al, 2014;Matsuoka et al, 2009;Zhou et al, 2009). This 20 aa deletion was not found in the NA stalk of SC-H5N6 and the human-H5N6 strain.…”
mentioning
confidence: 99%